Fragility – Sustainability: Two Conflicting Major Challenges of this Twenty-First Century - Argyriades, Demetrios; Kim, Pan Suk (Mercados y Negocios, 2019)
With the Great Recession receding, but crises still afflicting large swaths of the world and a climate of rampant distrust adversely affecting governance, it may be time to ask whether and, if so, how and where our field went wrong. Have we been willing victims of sleep-walkers using metaphors as models? This paper argues as much. Specifically, it contends that, foisted on the world as the one- size-fits-all prescription for good governance, nationally and internationally, it has ended turning governance and democracy on their heads, while also undermining the very foundations on which a global order, based on peaceful coexistence and constructive cooperation through the United Nations, was predicated. The prevalence of symptoms of hurt and discontent should lead us to conclude that the roots of our predicament and problems go much deeper, to a might counter- culture, which triumphed in the 1990s but still goes strong, in places.